Audio steganography by quantization index modulation in the DCT domain - CHEN Ming1; ZHANG Ru1; LIU Fan-fan1; NIU Xin-xin1; YANG Yi-xian1 (Tongxin xuebao)
Audio signal has more information redundancy than image signal, but its randomicity is stronger. It is more challenge to extract embedded bit with non-error from audio. A novel audio steganography based on QIM （quantization index modulation） in the DCT （discrete cosine transform） domain was proposed. The merits of the algorithm were as follows: based on the principle of QIM, the message was embedded by quantization method and was extracted by the map-ping between message bit and quantization interval. The extraction was executed blindly; the robustness of the hidden message was ensured well by the improved QIM, which employed the error-tolerance operation during embedding and extracting; the capacity was large as 357.6bit/s. The experimental results show that the proposed method achieves better imperceptivity than normal QIM and the SNR （signal to noise ratio） of the stego audio with the embedding rate of 100% is above 30dB. The embedded message has good robustness against MP3 compression, requantization, resampling and lowpass filtering. Moreover, the algorithm is easy to implement and highly practicable.